On the analytical investigation of fields and power patterns in coaxial omniguiding Bragg fibers - IBRAHIM, A; CHOUDHURY, P; ALIAS, M (2006)
Plots of the electric fields in the different sections of multilayered coaxial omniguiding Bragg fibers are presented. Investigations are made for the different dimensional values of the fiber, and a comparative study is made. It is found that the fields match very smoothly at the layer interfaces, and decay with the increase in radial distance. Particularly, field patterns are best matched in the case of large core Bragg fibers. For illustration, plots of power are also presented for two-layer and four-layer (core-clad) sections of the fiber. Power peaks are observed in both the types of fiber sections, and in this case also, it is observed that the power patterns match smoothly at the layer boundaries. Smooth match of fields as well as power patterns justifies the validity of the analytical procedure that implements the theory of Bloch formulation in omniguiding fibers. (c) 2005 Elsevier GmbH. All rights reserved.